PELATIHAN PEMBUATAN MEDIA PROMOSI BERBASIS WEB, PENINGKATAN KEWIRAUSAHAAN DAN MANAJEMEN PEMASARAN PADA KELOMPOK KELOMPOK PENGRAJIN TANJUNG PIAYU DI KOTA BATAM - Dian Lestari Siregar; Yuliadi Yuliadi; Rahmat Fauzi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
One sector of the small business group that is developing in the city of Batam is the Asoka craftsmen group located in Tanjung Piayu, the sustainable blue Pancur housing complex, Batam City. This group of craftsmen is a home-based business group that is mostly carried out by the community in Tanjung Piayu, Batam City, one of the sectors that are the target of product sales of this group is tourists visiting Batam city. The problems faced by this group of Asoka craftsmen include low levels of sales, and weakness in the marketing aspects of the product, especially in the sales distribution channel for their products. This PKM activity aims to expand the market share of the Asoka craftsmen group through web-based promotional media training, Increase productivity, Increase entrepreneurial expertise and skills, Increase expertise and skills through assistance in marketing handicraft products. The method of activities in this PKM includes training (web creation and operation, product stimulus assistance, entrepreneurship training, and marketing management training and assistance). The results of PKM activities for the Asoka craftsmen group were the availability of web-based promotional media so that the market share of the Ashoka craftsmen group's products became wider, increased productivity of the Asoka craftsmen group, and increased expertise and skills in marketing handicraft products.